ANALISIS POLITIK TERHADAP PROSES PENETAPAN PERATURAN DAERAH NOMOR 12 TAHUN 2013 TENTANG LARANGAN MEMPRODUKSI DAN MENGEDARKAN SERTA MENGGUNAKAN MINUMAN BERALKOHOL DI KABUPATEN BATANG - Emillia Rizky E. L; Susilo Utomo; Sulistyowati . (Journal of Politic and Government Studies, 2015)
Regional Regulation No. 12 of 2013 is a regulation that regulates and prohibits all forms of activities related to alcohol and applicable in the district of Batang. Determination of Regulation No. 12 of 2013 to attract successful when the regulation is set after a fairly difficult process, which is used quite a long time, the bergaining of the actors, the pros and cons that occur in the community, as well as the conditions and situations, Batang were bypassed by pantura path. Researchers try to analyze what happened and who the actors that play a role in the regulation-setting process.The purpose of this study to determine the dynamics of the process of the formulation to the determination of the law. This research is a type of qualitative research. The data is taken through the interview process and document Parliament Secretariat, Batang.Based on the results of this research is that executives who initiative emergence of regulation on the prohibition of alcohol at the insistence of some interest groups. In the process of formulating regulations also note the presence of bergaining between actors who support and reject the establishment of legislation on the prohibition of alcohol. Actors supporting the adoption of regulations on alcohol ban propose policy alternatives that reads a total ban. While the actor who refused fixing regulations to control reads the policy alternatives. Research has been done to provide information based on the clarification of that Regulation No. 12 of 2013 should be revised to conform with the Presidential Decree No. 74 of 2013. The actor who played a major role in the regulation-setting process is the initiative of the executive as well as interest groups supporting the adoption of regulations. The model used to analyze the process of determining the author uses a model of the Policy Analysis process in which the authors analyze the various stages in the process of lawmaking No. 12 of 2013. While the process used by the actors in formulating and establishing Regulation No. 12 of 2013 is a model of group which interest groups has a major role in any process.